Mapping the Scene and Object Processing Networks by Intracranial EEG - Vlcek, Kamil; Fajnerova, Iveta; Nekovarova, Tereza; Hejtmanek, Lukas; Janca, Radek; Jezdik, Petr; Kalina, Adam; Tomasek, Martin; Krsek, Pavel; Hammer, Jiri; Marusic, Petr (Frontiers in Human Neuroscience, 2020)
Human perception and cognition are based predominantly on visual information processing. Much of the information regarding neuronal correlates of visual processing has been derived from functional imaging studies, which have identified a variety of brain areas contributing to visual analysis, recognition and processing of objects and scenes. However, only two of these areas, namely the parahippocampal place area and the lateral occipital complex, were verified and further characterized by intracranial electroencephalogram (iEEG). iEEG is a unique measurement technique that samples a local neuronal population with high temporal and anatomical resolution. In the present study, we aimed to expand on previous reports and examine brain activity for selectivity of scenes and objects in the broadband high-gamma frequency range (50 - 150 Hz). We collected iEEG data from 27 epileptic patients while they watched a series of images, containing objects and scenes, and we identified 375 bipolar channels responding to at least one of these two categories. Using K-means clustering, we delineated their brain localization. In addition to the two areas described previously, we detected significant responses in two other scene-selective areas, not yet reported by any electrophysiological studies; namely the occipital place area and the retrosplenial complex. Moreover, using iEEG we revealed a much broader networks underlying visual processing than that described to date, using specialized functional imaging experimental designs. Here we report the selective brain areas for scene processing include the posterior collateral sulcus and the anterior temporal region, which were already shown to be related to scene novelty and landmark naming. The object-selective responses appeared in the parietal, frontal, and temporal regions connected with tool use and object recognition. The temporal analyses specified the time course of the category selectivity through the dorsal and ventral visual streams. The receiver operating characteristic analyses identified the parahippocampal place area and the fusiform portion of the lateral occipital complex as being the most selective for scenes and objects, respectively. Our findings represent a valuable overview of visual processing selectivity for scenes and objects based on iEEG analyses and thus, contribute to a better understanding of visual processing in the human brain.